2019
DOI: 10.4102/sajp.v75i1.683
|View full text |Cite
|
Sign up to set email alerts
|

Level of knowledge, attitudes and beliefs towards patients with chronic low back pain among final year School of Therapeutic Sciences students at the University of the Witwatersrand – A cross-sectional study

Abstract: Background: Knowledge of neurophysiology of pain influences healthcare providers’ attitudes and beliefs about patients with chronic low back pain which affect management choices.Objectives: The aim of this study was to determine the level of knowledge of pain and attitudes and beliefs towards patients with chronic low back pain among final year undergraduate students from the School of Therapeutic Sciences at the University of the Witwatersrand.Methods: This cross-sectional study included two questionnaires – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
7
2
Order By: Relevance
“…This level of knowledge was comparable to that in other studies using the RPNQ. For example, our score was similar to a previous study among Saudi PT students with a mean score of 6.2 in the same questionnaire (51.6%) (Alodaibi et al 2018) and similar to the score of South African PT students in their nal year (58%) (Mukoka et al 2019). Further, our score was comparable to the 55% score reported for untrained healthcare professionals (PT, occupational therapists, psychologists, and rehabilitation counsellors) in Australia (Moseley 2004).…”
Section: Discussionsupporting
confidence: 88%
“…This level of knowledge was comparable to that in other studies using the RPNQ. For example, our score was similar to a previous study among Saudi PT students with a mean score of 6.2 in the same questionnaire (51.6%) (Alodaibi et al 2018) and similar to the score of South African PT students in their nal year (58%) (Mukoka et al 2019). Further, our score was comparable to the 55% score reported for untrained healthcare professionals (PT, occupational therapists, psychologists, and rehabilitation counsellors) in Australia (Moseley 2004).…”
Section: Discussionsupporting
confidence: 88%
“…3 Approximate hours of pain education teaching in each discipline and University generally concur with the existing body of literature that suggests there is a deficiency in pain knowledge and attitudes towards pain in final year HCP students. Many previous studies noted an improvement in HCP students' knowledge and attitudes from first to final year [37,38,62,64,65], and while we found this among physiotherapy students, it was not the case overall. Worryingly, Ryan et al, (2010) [61] noted that non-health care students demonstrated a 3.9 point 3.7% mean difference in HC-PAIRS 15-point questionnaire from first to final year.…”
Section: Discussioncontrasting
confidence: 75%
“…Whilst Carroll et al, (2020) [40] found greater improvement amongst their nursing cohorts' attitudes (1.6%-7% amongst different nursing specialities) than in this study, 2.4%, our findings accord with Amponsah et al (2020) [62] and Leahy et al (2019) [63] that final year nurses have considerable deficits in pain knowledge and attitudes. Mukoka, Olivier and Ravat (2019) [64] found more positive attitudes in their nursing and occupational therapy students but not as positive among their physiotherapy students. Overall the findings from this study Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, the score was lower than that of Portuguese and Spanish PT students in their final year who attended formative active teaching sessions to improve their knowledge of pain neurophysiology. Those students scored 62.5% [ 23 ] and 68.92% [ 11 ], respectively, on the RNPQ.…”
Section: Discussionmentioning
confidence: 99%